Palladium- and nickel-catalyzed cascade enantioselective ring-opening/coupling reactions of cyclobutanones - Cao, Jian; Xu, Li-Wen (Chemical communications (Cambridge, England), 2023)
The chemistry of small ring compounds is an intriguing subject in organic chemistry. As the smallest stable cyclic aliphatic ketones, cyclobutanones have garnered tremendous attention owing to their intrinsic high reactivity such as transition-metal catalyzed C-C bond cleavage. In this context, transition-metal catalyzed formal cycloaddition of cyclobutanones via a "cut and sew" strategy has gained marvelous advances. In contrast, an alternative reaction paradigm, i.e. , transition-metal catalyzed ring-opening reactions of cyclobutanones, is still underdeveloped. This feature article aims to summarize our efforts in developing enantioselective palladium-catalyzed ring-opening/coupling reactions and recently emerging nickel-catalyzed ring-opening/reductive coupling reactions of cyclobutanones with a tethered aryl halide. The possible mechanisms are briefly showcased and the advantages and limitations of each strategy as well as their synthetic applications in the synthesis of natural products or bioactive compounds are presented. This article summarizes recent efforts in developing enantioselective palladium- and nickel-catalyzed ring-opening/coupling reactions of cyclobutanones with a tethered aryl halide.